Image Semiotics in the Book "Our Arabic Language" for the Third Grade in Jordan: An Analytical Study using Human and Artificial Intelligence - Bani Omar, Khitam Ahmad (European Scientific Journal, ESJ, 2023)
This paper focuses on identifying the image semiotics in the textbook “Our Arabic Language” for the third grade in Jordan, employing both human intelligence and artificial intelligence. To achieve the study objectives, a content and semiotic analysis method was adopted using human and artificial intelligence. The study sample consisted of 20 images, which represents the entire study population within the Arabic language textbook for third-grade students. The most prominent results revealed a male bias in terms of the number of characters, functional roles, social roles, talents, and activities. There was a convergence between the semiotic analysis using human intelligence and semiotic analysis using artificial intelligence. The results also showed that there were differences in the results of the semiotic analysis between the use of artificial intelligence and the use of human intelligence. This is because the human analysis connects images with social context and other images, while the artificial intelligence deals with every image separately.